Magnesium phosphate cement-based concrete and preparation method thereof
By designing a multi-layer corrosion-resistant structure in magnesium phosphate cement-based concrete, combining nanomaterials and functional fibers, the corrosion and penetration problems of existing materials in complex and harsh environments are solved, and significant improvements in durability and environmental adaptability are achieved.
Patent Information
- Application Number
- CN202411795758.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
The existing magnesium phosphate cement-based materials have technical bottlenecks in corrosion resistance and penetration resistance, and it is difficult to meet the needs of use in complex and harsh environments.
By rationally preparing magnesium phosphate cement-based concrete, a multi-layer corrosion-resistant structure design is adopted, including matrix modification, interface enhancement, densified structure and intelligent ion barrier, combined with nanomaterials and functional fibers, a comprehensive corrosion-resistant barrier is formed.
It realizes multi-layer corrosion-resistant barrier, dense microstructure, intelligent ion barrier and good environmental adaptability, significantly improving the durability and adaptability of the material, and is suitable for complex and harsh environments.
Abstract
Description
Technical Field
[0001] The invention relates to concrete, in particular to magnesium phosphate cement-based concrete and a preparation method thereof. Background Art
[0002] With the rapid development of infrastructure, the requirements for material durability and environmental adaptability are increasing. Traditional silicate cement-based high-performance concrete is difficult to meet the high durability requirements in extreme corrosive environments such as the ocean and chemical industry. Magnesium phosphate cement (MPC) has excellent properties such as high early strength, low-temperature curing, and acid and alkali corrosion resistance. Combining it with ultra-high performance concrete (UHPC) is expected to significantly improve the durability of the material. However, the existing MPC-based materials still have certain technical bottlenecks in terms of corrosion resistance and anti-penetration. It is necessary to achieve a multi-level anti-corrosion barrier through material modification and structural optimization to meet the needs of special environments. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a magnesium phosphate cement-based concrete, which has a multi-layered anti-corrosion barrier, a dense microstructure, an intelligent ion barrier and good environmental adaptability, and can meet the use requirements in complex and harsh environments.
[0004] In order to solve the above technical problems, the technical solution of the present invention is:
[0005] A magnesium phosphate cement-based concrete is made of the following raw materials in parts by weight: 10-20 parts of phosphate, 30-50 parts of active magnesium oxide, 0.5-3 parts of retarder, 5-15 parts of mineral admixture, 0.5-4 parts of functional additive, 20-30 parts of fine aggregate, 2-5 parts of reinforcing fiber, and 10-28 parts of water. Phosphate is one of the main components of magnesium phosphate cement, which is used to react with active magnesium oxide to form a hydration product; active magnesium oxide is used as a reaction component to react with dihydrogen phosphate to produce a hydration product to improve the strength and density of the material; the retarder is used to regulate the rate of the hydration reaction and improve the durability of the material.
[0006] Furthermore, the phosphate described in the present invention is one of magnesium dihydrogen phosphate, ammonium dihydrogen phosphate or potassium dihydrogen phosphate.
[0007] Furthermore, the retarder of the present invention is one of calcium hydroxide, sodium hexametaphosphate or sodium tripolyphosphate.
[0008] Furthermore, the mineral admixture of the present invention is one of nano silicon dioxide, silica ash or ultrafine fly ash, the particle size of nano silicon dioxide is 90-100nm, the particle size of silica ash is 0.5-1μm, and the particle size of ultrafine fly ash is 1-5μm.
[0009] Furthermore, the functional additive of the present invention is one of nano titanium dioxide, hydrotalcite or calcium phosphate, the particle size of nano titanium dioxide is 40nm, and the chemical formula of hydrotalcite is Mg6Al2(OH) 16 CO3·4H2O. Among them, nano titanium dioxide is used to improve the self-cleaning and durability of the material, hydrotalcite is used to adsorb and fix corrosive ions such as chloride ions, and calcium phosphate is used to form a dense structure and improve the acid resistance of the material.
[0010] Furthermore, the fine aggregate of the present invention is quartz sand with a particle size of 200-500 μm.
[0011] Furthermore, the reinforcing fiber of the present invention is one of PVA fiber, polypropylene fiber or basalt fiber pretreated with a silane coupling agent. Furthermore, the monofilament diameter of the PVA fiber, polypropylene fiber or basalt fiber is 10-20 μm, and the monofilament length is 6-12 mm. The preparation steps of the PVA fiber, polypropylene fiber or basalt fiber pretreated with a silane coupling agent are:
[0012] (1) Cleaning the fiber surface to ensure that the fiber surface is clean and provide active sites for the adsorption and reaction of the silane coupling agent. First, soak the fiber (PVA fiber, polypropylene fiber or basalt fiber with a single fiber diameter of 10-20μm and a single fiber length of 6-12mm) in deionized water and ultrasonically clean it to remove surface impurities and oil stains; then use ethanol or acetone for a second cleaning to further remove surface pollutants; then dry the fiber at room temperature or dry it at low temperature (50-60℃).
[0013] (2) Preparation of silane coupling agent solution: Select a silane coupling agent suitable for the fiber (such as γ-aminopropyl triethoxysilane KH-550, γ-methacryloxypropyl trimethoxysilane KH-570 or vinyl triethoxysilane VTES, KH-550 can be selected for PVA fiber, KH-570 can be selected for polypropylene fiber, and KH-550 or VTES can be selected for basalt fiber), prepare an aqueous solution of 1-2% (volume fraction) of the silane coupling agent, dissolve the silane coupling agent in deionized water, adjust the pH value to 4-5 with acetic acid or dilute hydrochloric acid, stir until completely transparent, and let it stand for 30 minutes to ensure that the silane coupling agent is fully hydrolyzed to obtain a silane coupling agent solution.
[0014] (3) Fiber impregnation: through the hydrolysis and condensation reaction of the silane coupling agent, a silicon-oxygen bond is formed on the fiber surface to enhance the interfacial bonding force. The fiber (PVA fiber, polypropylene fiber or basalt fiber) treated in step (1) is immersed in the silane coupling agent solution obtained in step (2) for 20-30 minutes to ensure that the silane coupling agent is fully adsorbed on the fiber surface.
[0015] (4) Fiber drying to ensure that the silane coupling agent is firmly attached to the fiber surface and forms a uniform coating: the fiber treated in step (3) is taken out and rinsed with deionized water to remove unreacted silane coupling agent; then dried in a constant temperature oven at 60° C. for 2-4 hours to ensure that a stable silane coating is formed on the surface, thereby obtaining PVA fiber, polypropylene fiber or basalt fiber pretreated with a silane coupling agent.
[0016] Another technical problem to be solved by the present invention is to provide a method for preparing the magnesium phosphate cement-based concrete.
[0017] To solve the above technical problems, the technical solution is:
[0018] A method for preparing magnesium phosphate cement-based concrete comprises the following steps:
[0019] S1. Weigh each raw material by weight, dissolve the phosphate in water, stir at low speed until mixed, add active magnesium oxide and retarder, continue stirring at low speed until mixed to obtain a mixture;
[0020] S2. Add the mineral admixture, functional additives and fine aggregate to the mixture obtained in step S1, and stir at medium speed until the mixture is uniformly mixed to obtain a mixture II;
[0021] S3. The reinforcing fiber is added to the mixture obtained in step S2, and stirring is continued at medium speed for 2-3 minutes to obtain a mixed slurry;
[0022] S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
[0023] Furthermore, in step S1 of the present invention, the stirring speed of the low-speed stirring is 120-150 rpm; in steps S2 and S3, the stirring speed of the medium-speed stirring is 270-300 rpm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) Multi-layer protection structure: Based on the main component materials of the magnesium phosphate cement-based concrete, the present invention forms a multi-layer anti-corrosion structure in the matrix, interface and surface of the material, constructing an all-round anti-corrosion barrier with significant durability from microstructure to macro performance:
[0026] i. Matrix modification layer: through the filling of mineral admixtures (such as nano-silicon dioxide, etc.) and microstructure optimization, the density of the matrix is improved, and the porosity and connectivity of the capillary channels are reduced;
[0027] ii. Interface reinforcement layer: Silane coupling agent is used to treat the interface between fiber and matrix to enhance the bonding performance between fiber and matrix and improve the crack resistance and impermeability of the material. One end of the silane coupling agent molecule contains a siloxane group (Si-O), which can react with the hydroxyl group on the surface of the inorganic matrix (such as MPC magnesium phosphate cement) to form a strong chemical bond, and the other end contains an organic functional group, which can react with organic fibers (such as PVA fibers, polypropylene fibers, etc.) or form physical adsorption to improve the interface bonding force. Therefore, the silane coupling agent can improve the interface performance between the fiber and the cement matrix, enhance the interface bonding force between the fiber and the MPC matrix, and improve the crack resistance, toughness and overall durability.
[0028] (2) Densified structure design: Through the low water-to-binder ratio design, combined with ultrafine mineral admixtures such as nano-silica with high specific surface area, the porosity is reduced to a minimum, ensuring that the microstructure inside the material is dense. At the same time, products such as calcium phosphate and magnesium phosphate generated during the hydration process of the material are further deposited in the pores, improving the material's anti-penetration performance and ensuring that it is not easily corroded in water, acid and alkali environments.
[0029] (3) Intelligent ion barrier: By adding ion adsorption materials (such as hydrotalcite), an adsorption barrier for chloride ions and sulfate ions is formed, which can effectively inhibit the corrosive ions from entering the interior of the material. The resistance of the present invention to chloride ions and sulfate ions in corrosive media is significantly improved, and it can be used in corrosive environments such as the ocean, avoiding the corrosion defects of traditional cement materials.
[0030] (4) Enhanced environmental adaptability: In order to improve the adaptability of the material in high humidity and acid-base environments, the present invention adds mineral components such as calcium phosphate so that the material can still maintain stable physical and chemical properties in a humid or acid-base environment, and has good low-temperature curing and humidity stability. It has excellent durability in coastal areas, industrial pollution areas and other areas, and is suitable for construction needs in coastal areas, industrial pollution environments and low temperature conditions.
[0031] (5) The present invention has excellent corrosion resistance, anti-penetration and environmental adaptability, and is suitable for infrastructure and important building structures in harsh corrosive environments. The stability of the material performance of the present invention can greatly reduce maintenance costs and environmental impacts, extend the life of the project, and achieve comprehensive benefits of high efficiency, environmental protection and economy. DETAILED DESCRIPTION
[0032] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention but are not intended to limit the present invention.
[0033] Example 1
[0034] The magnesium phosphate cement-based concrete is prepared from the following raw materials in parts by weight: 10 parts of magnesium dihydrogen phosphate, 40 parts of active magnesium oxide, 3 parts of calcium hydroxide, 2 parts of nano silicon dioxide with a particle size of 90-100 nm, 3 parts of silica fume with a particle size of 0.5-1 μm, 3 parts of calcium phosphate, 20 parts of quartz sand with a particle size of 200-500 μm, 3 parts of PVA fibers pretreated with a silane coupling agent KH550, and 15 parts of water.
[0035] The preparation steps of PVA fiber pretreated with silane coupling agent KH550 are as follows:
[0036] (1) First, PVA fibers with a monofilament diameter of 10-20 μm and a monofilament length of 6-12 mm are immersed in deionized water and ultrasonically cleaned, then cleaned twice with ethanol, and then the PVA fibers are dried at room temperature.
[0037] (2) Dissolve the silane coupling agent KH550 in deionized water, adjust the pH value to 4.5 with dilute hydrochloric acid, stir until completely transparent, and let stand for 30 minutes to obtain a silane coupling agent solution with a volume fraction of 1%.
[0038] (3) Immerse the PVA fiber treated in step (1) in the silane coupling agent solution obtained in step (2) for 25 minutes.
[0039] (4) The PVA fiber treated in step (3) is taken out and rinsed with deionized water; then, it is dried in a constant temperature oven at 60° C. for 3 hours to obtain the PVA fiber pretreated with silane coupling agent KH550.
[0040] The preparation method of Example 1 comprises the following steps:
[0041] S1. Weigh each raw material in parts by weight, dissolve magnesium dihydrogen phosphate in water, stir at a stirring speed of 140rpm until mixed, then add active magnesium oxide and calcium hydroxide, stir at a stirring speed of 140rpm until mixed to obtain a mixture;
[0042] S2. The nano-silicon dioxide, silica fume, calcium phosphate and quartz sand were added to the mixture obtained in step S1, and stirred at a stirring speed of 280 rpm until the mixture was uniformly mixed to obtain a mixture II;
[0043] S3. The PVA fiber treated with silane coupling agent KH550 was added to the mixture obtained in step S2, and the mixture was stirred at a medium speed of 280 rpm for 2.5 minutes to obtain a mixed slurry;
[0044] S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
[0045] Example 2
[0046] Magnesium phosphate cement-based concrete is made of the following raw materials in parts by weight: 10 parts of magnesium dihydrogen phosphate, 35 parts of active magnesium oxide, 1 part of sodium hexametaphosphate, 3 parts of nano silicon dioxide with a particle size of 90-100 nm, 2 parts of ultrafine fly ash with a particle size of 1-5 μm, and 0.5 parts of nano titanium dioxide with a particle size of 40-60 nm. The chemical formula is Mg6Al2(OH) 16 1.5 parts of CO3·4H2O hydrotalcite, 25 parts of quartz sand of 200-500 μm, 3 parts of polypropylene fiber pretreated with silane coupling agent KH570, and 13.5 parts of water.
[0047] The preparation steps of polypropylene fiber pretreated with silane coupling agent KH570 are as follows:
[0048] (1) First, a polypropylene fiber with a monofilament diameter of 10-20 μm and a monofilament length of 6-12 mm is immersed in deionized water and ultrasonically cleaned, then cleaned twice with acetone, and then dried at 50°C.
[0049] (2) Dissolve the silane coupling agent KH570 in deionized water, adjust the pH value to 4 with acetic acid, stir until completely transparent, and let stand for 30 minutes to obtain a silane coupling agent solution with a volume fraction of 1.5%.
[0050] (3) The polypropylene fiber treated in step (1) is immersed in the silane coupling agent solution obtained in step (2) for 30 minutes.
[0051] (4) The polypropylene fiber treated in step (3) is taken out and rinsed with deionized water; then, it is dried in a constant temperature oven at 60° C. for 4 hours to obtain a polypropylene fiber pretreated with a silane coupling agent KH570.
[0052] The preparation method of Example 2 comprises the following steps:
[0053] S1. Weigh the raw materials in parts by weight, dissolve magnesium dihydrogen phosphate in water, stir at a stirring speed of 120rpm until mixed, then add activated magnesium oxide and sodium hexametaphosphate, stir at a stirring speed of 120rpm until mixed to obtain a mixture;
[0054] S2. The nano-silicon dioxide, ultrafine fly ash, nano-titanium dioxide, hydrotalcite, quartz sand are added to the mixture obtained in step S1, and stirred at a stirring speed of 270rpm until the mixture is uniformly mixed to obtain a mixture II;
[0055] S3. The polypropylene fiber treated with silane coupling agent KH570 was added to the mixture obtained in step S2, and the mixture was stirred at a medium speed of 270 rpm for 2 minutes to obtain a mixed slurry;
[0056] S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
[0057] Example 3
[0058] The magnesium phosphate cement-based concrete is prepared from the following raw materials in parts by weight: 15 parts of magnesium dihydrogen phosphate, 40 parts of active magnesium oxide, 0.5 parts of sodium tripolyphosphate, 2 parts of nano silicon dioxide with a particle size of 90-100 nm, 3 parts of silica fume with a particle size of 0.5-1 μm, 4 parts of calcium phosphate, 20 parts of quartz sand with a particle size of 200-500 μm, 4 parts of basalt fiber pretreated with a silane coupling agent VTES, and 15.2 parts of water.
[0059] The preparation steps of basalt fiber pretreated with silane coupling agent VTES are as follows:
[0060] (1) First, basalt fibers with a single fiber diameter of 10-20 μm and a single fiber length of 6-12 mm are immersed in deionized water and ultrasonically cleaned, then cleaned twice with acetone, and then dried at 60° C.
[0061] (2) Dissolve the silane coupling agent VTES in deionized water, adjust the pH value to 4 with acetic acid, stir until completely transparent, and let stand for 30 minutes to obtain a silane coupling agent solution with a volume fraction of 2%.
[0062] (3) Immerse the basalt fiber treated in step (1) in the silane coupling agent solution obtained in step (2) for 30 minutes.
[0063] (4) taking out the basalt fiber treated in step (3), rinsing it with deionized water; and then drying it in a constant temperature oven at 60° C. for 2 hours to obtain a basalt fiber pretreated with a silane coupling agent VTES.
[0064] The preparation method of Example 3 comprises the following steps:
[0065] S1. Weigh the raw materials in parts by weight, dissolve magnesium dihydrogen phosphate in water, stir at a stirring speed of 150rpm until mixed, then add active magnesium oxide and sodium tripolyphosphate, stir at a stirring speed of 150rpm until mixed to obtain a mixture;
[0066] S2. The nano-silicon dioxide, silica fume, calcium phosphate and quartz sand are added to the mixture obtained in step S1, and stirred at a stirring speed of 300 rpm until the mixture is uniformly mixed to obtain a mixture II;
[0067] S3. The basalt fiber treated with silane coupling agent VTES was added to the mixture obtained in step S2, and the mixture was stirred at a medium speed of 300 rpm for 3 minutes to obtain a mixed slurry;
[0068] S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
[0069] Experimental example:
[0070] The magnesium phosphate cement-based concrete prepared in Examples 1-3 was tested for compressive strength and tensile strength according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB / T 50081-2019, and the impermeability grade and chloride ion penetration depth (immersed in a salt water environment for 60 days) were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GB / T 50082-2009. The test results are shown in Table 1:
[0071] Compressive strength(MPa) Tensile strength(MPa) Impermeability grade Chloride ion penetration depth (mm) Example 1 170 20 P12 0.1 Example 2 180 22 P13 0.1 Example 3 185 23 P14 0.1
[0072] Table 1
[0073] From Table 1, the compressive strength, tensile strength and impermeability grade of Examples 1-3 are all high, and the chloride ion penetration depth is all small, indicating that the magnesium phosphate cement-based concrete prepared by the present invention has good corrosion resistance, impermeability and strong mechanical properties.
[0074] Example 4
[0075] Magnesium phosphate cement-based concrete is made of the following raw materials in parts by weight: 20 parts of ammonium dihydrogen phosphate, 50 parts of active magnesium oxide, 0.5 parts of calcium hydroxide, 4 parts of nano-silicon dioxide with a particle size of 90-100nm, 3 parts of silica fume with a particle size of 0.5-1μm, and 2 parts of nano-titanium dioxide with a particle size of 40-60nm. The chemical formula is Mg6Al2(OH) 16 2 parts of CO3·4H2O hydrotalcite, 24 parts of quartz sand of 200-500 μm, 5 parts of basalt fiber pretreated with silane coupling agent KH550, and 28 parts of water.
[0076] The preparation steps of basalt fiber pretreated with silane coupling agent KH550 are as follows:
[0077] (1) First, basalt fibers with a single fiber diameter of 10-20 μm and a single fiber length of 6-12 mm are immersed in deionized water and ultrasonically cleaned, then cleaned twice with acetone, and then dried at 60° C.
[0078] (2) Dissolve the silane coupling agent KH550 in deionized water, adjust the pH value to 4 with acetic acid, stir until completely transparent, and let stand for 30 minutes to obtain a silane coupling agent solution with a volume fraction of 1%.
[0079] (3) Immerse the basalt fiber treated in step (1) in the silane coupling agent solution obtained in step (2) for 25 minutes.
[0080] (4) The basalt fiber treated in step (3) is taken out and rinsed with deionized water; then, it is dried in a constant temperature oven at 60° C. for 3 hours to obtain basalt fiber pretreated with silane coupling agent KH550.
[0081] The preparation method of Example 4 comprises the following steps:
[0082] S1. Weigh each raw material in parts by weight, dissolve ammonium dihydrogen phosphate in water, stir at a low speed of 150rpm until mixed, then add activated magnesium oxide and calcium hydroxide, stir at a low speed of 150rpm until mixed to obtain a mixture;
[0083] S2. The nano-silica, silica fume, nano-titanium dioxide, hydrotalcite, quartz sand are added to the mixture obtained in step S1, and stirred at a stirring speed of 300 rpm until the mixture is uniformly mixed to obtain a mixture II;
[0084] S3. The basalt fiber treated with silane coupling agent KH550 was added to the mixture obtained in step S2, and the mixture was stirred at a medium speed of 300 rpm for 3 minutes to obtain a mixed slurry;
[0085] S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
[0086] Example 5
[0087] Magnesium phosphate cement-based concrete is made of the following raw materials in parts by weight: 12 parts of potassium dihydrogen phosphate, 30 parts of active magnesium oxide, 0.2 parts of sodium hexametaphosphate, 10 parts of nano silicon dioxide with a particle size of 90-100 nm, 5 parts of ultrafine fly ash with a particle size of 1-5 μm, and 0.2 parts of nano titanium dioxide with a particle size of 40-60 nm. The chemical formula is Mg6Al2(OH) 16 0.3 parts of CO3·4H2O hydrotalcite, 30 parts of quartz sand of 200-500 μm, 2 parts of polypropylene fiber pretreated with silane coupling agent KH570, and 10 parts of water.
[0088] The preparation steps of polypropylene fiber pretreated with silane coupling agent KH570 are as follows:
[0089] (1) First, a polypropylene fiber with a monofilament diameter of 10-20 μm and a monofilament length of 6-12 mm is immersed in deionized water and ultrasonically cleaned, then cleaned twice with acetone, and then dried at 50°C.
[0090] (2) Dissolve the silane coupling agent KH570 in deionized water, adjust the pH value to 3 with acetic acid, stir until completely transparent, and let stand for 30 minutes to obtain a silane coupling agent solution with a volume fraction of 1%.
[0091] (3) The polypropylene fiber treated in step (1) is immersed in the silane coupling agent solution obtained in step (2) for 20 minutes.
[0092] (4) The polypropylene fiber treated in step (3) is taken out and rinsed with deionized water; then, it is dried in a constant temperature oven at 60° C. for 3 hours to obtain a polypropylene fiber pretreated with a silane coupling agent KH570.
[0093] The preparation method of Example 5 comprises the following steps:
[0094] S1. Weigh the raw materials in parts by weight, dissolve potassium dihydrogen phosphate in water, stir at a stirring speed of 120rpm until mixed, then add activated magnesium oxide and sodium hexametaphosphate, stir at a stirring speed of 120rpm until mixed to obtain a mixture;
[0095] S2. The nano-silicon dioxide, ultrafine fly ash, nano-titanium dioxide, hydrotalcite, quartz sand are added to the mixture obtained in step S1, and stirred at a stirring speed of 270rpm until the mixture is uniformly mixed to obtain a mixture II;
[0096] S3. The polypropylene fiber treated with silane coupling agent KH570 was added to the mixture obtained in step S2, and the mixture was stirred at a medium speed of 270 rpm for 2 minutes to obtain a mixed slurry;
[0097] S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
[0098] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A magnesium phosphate cement-based concrete, characterized in that: The concrete is prepared from the following raw materials in parts by weight: 10-20 parts of phosphate, 30-50 parts of active magnesium oxide, 0.5-3 parts of retarder, 5-15 parts of mineral admixture, 0.5-4 parts of functional additive, 20-30 parts of fine aggregate, 2-5 parts of reinforcing fiber and 10-28 parts of water.
2. A magnesium phosphate cement-based concrete according to claim 1, characterized in that: The phosphate is one of magnesium dihydrogen phosphate, ammonium dihydrogen phosphate or potassium dihydrogen phosphate.
3. A magnesium phosphate cement-based concrete according to claim 1, characterized in that: The retarder is one of calcium hydroxide, sodium hexametaphosphate or sodium tripolyphosphate.
4. A magnesium phosphate cement-based concrete according to claim 1, characterized in that: The mineral admixture is one of nano silicon dioxide, silica ash or ultrafine fly ash. The particle size of nano silicon dioxide is 90-100nm, the particle size of silica ash is 0.5-1μm, and the particle size of ultrafine fly ash is 1-5μm.
5. A magnesium phosphate cement-based concrete according to claim 1, characterized in that: The functional additive is one of nano titanium dioxide, hydrotalcite or calcium phosphate. The particle size of nano titanium dioxide is 40nm. The chemical formula of hydrotalcite is Mg6Al2(OH) 16 CO3·4H2O.
6. A magnesium phosphate cement-based concrete according to claim 1, characterized in that: The fine aggregate is quartz sand with a particle size of 200-500 μm.
7. The magnesium phosphate cement-based concrete according to claim 1, characterized in that: The reinforcing fiber is one of PVA fiber, polypropylene fiber or basalt fiber pretreated with a silane coupling agent.
8. A magnesium phosphate cement-based concrete according to claim 7, characterized in that: The monofilament diameter of the PVA fiber, polypropylene fiber or basalt fiber is 10-20 μm, and the monofilament length is 6-12 mm.
9. The method for preparing magnesium phosphate cement-based concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh each raw material by weight, dissolve the phosphate in water, stir at low speed until mixed, add active magnesium oxide and retarder, continue stirring at low speed until mixed to obtain a mixture; S2. Add the mineral admixture, functional additives and fine aggregate to the mixture obtained in step S1, and stir at medium speed until the mixture is uniformly mixed to obtain a mixture II; S3. The reinforcing fiber is added to the mixture obtained in step S2, and stirring is continued at medium speed for 2-3 minutes to obtain a mixed slurry; S4. Pour the mixed slurry obtained in step S3 into a mold, vibrate to exhaust and shape it, and then demold after curing at room temperature for 24 hours to obtain magnesium phosphate cement-based concrete.
10. The method for preparing magnesium phosphate cement-based concrete according to claim 9, characterized in that: In step S1, the stirring speed of the low-speed stirring is 120-150 rpm; in steps S2 and S3, the stirring speed of the medium-speed stirring is 270-300 rpm.
Citation Information
Cited By
Modified magnesium phosphate cement grouting material as well as preparation method and application thereof
CN120590141A
Pavement patching material with high early strength and toughness and preparation method thereof
CN121135356A
Inorganic normal-temperature rapid-hardening coal-rock mass reinforcing and filling material
CN121872715A
Preparation process of marine concrete structure surface anti-erosion cement-based material
CN122254858A